Mono-oxime bisquaternary acetylcholinesterase reactivators with prop-1,3-diyl linkage-Preparation, in vitro screening and molecular docking - Musilek, Kamil; Komloova, Marketa; Holas, Ondrej; Horova, Anna; Pohanka, Miroslav; Gunn-Moore, Frank; Dohnal, Vlastimil; Dolezal, Martin; Kuca, Kamil (Bioorganic & medicinal chemistry, 2011)
The treatment of organophosphorus (OP) poisoning consists of the administration of a parasympatholytic agent (e.g., atropine), an anticonvulsant (e.g., diazepam) and an acetylcholinesterase (AChE) reactivator (e.g., obidoxime). The AChE reactivator is the causal treatment of OP exposure, because it cleaves the OP moiety covalently bound to the AChE active site. In this paper, fourteen novel AChE reactivators are described. Their design originated from a former promising compound K027. These compounds were synthesized, evaluated in vitro on human AChE (hAChE) inhibited by tabun, paraoxon, methylparaoxon and DFP and then compared to commercial hAChE reactivators (pralidoxime, HI-6, trimedoxime, obidoxime, methoxime) or previously prepared compounds (K027, K203). Three of these novel compounds showed a promising ability to reactivate hAChE comparable or better than the used standards. Consequently, a molecular docking study was performed for three of these promising novel compounds. The docking results confirmed the apparent influence of π-π or cation-π interactions and hydrogen bonding for reactivator binding within the hAChE active site cleft. The SAR features concerning the non-oxime part of the reactivator molecule are also discussed.
Keywords: Acetylcholinesterase; vodíková vazba; vazebná místa; počítačová simulace; Organophosphorus Compounds; oximy; Structure-Activity Relationship; lidé; organofosforové sloučeniny; Computer Simulation; Oximes; katalytická doména; acetylcholinesterasa; reaktivátory cholinesterasy; Hydrogen Bonding; vztahy mezi strukturou a aktivitou; Catalytic Domain; Cholinesterase Reactivators; Binding Sites; Humans